The Small Island States in the Indian Ocean: Perceptions, Concerns and Interests - Attanayake, Chulanee; Ranjan, Amit (AEI Insights, 2023)
With the emergence of China as a major economic power, the economic growth is shifting from the West to the East. China is also challenging the global power status quo. Consequently, there is a rapid change in the Indo-Pacific region where several regional and extra-regional powers are contesting and competing to attain strategic influence over the others. In such a situation, small states of the Indo-Pacific region have gained importance. While existing scholarly resources explore how the great power struggle is played in the Indian Ocean and how this impacts island states, little focus is given on how the island states perceive this change. Amidst this backdrop, this paper explores how small Indian Ocean island states perceive the Indo-Pacific. The article views the contestation and cooperation in the Indo-Pacific and explores small island states’ concerns and interests regarding the emerging Indo-Pacific Order. The paper uses four cases as examples, Sri Lanka, the Maldives, Seychelles and Mauritius.